Highly efficient p-i-n perovskite solar cells that endure temperature variations - Declan Hughes (Science, 2023)
Daily temperature variations induce phase transitions and lattice strains in halide perovskites, challenging their stability in solar cells. We stabilised the perovskite black phase and improved the solar cell performance using the ordered dipolar structure of β-poly(1,1-difluoroethylene) to control the perovskite film crystallisation and the energy alignment. We demonstrated p-i-n perovskite solar cells with a record power conversion efficiency of 24.6% over 18 square millimetres and 23.1% over 1 square centimetre, which retained 96% and 88% of the efficiency after 1000-hours 1-sun maximum power point tracking at 25 and 75 °C, respectively. Devices under rapid thermal cycling between −60 °C and +80 °C showed no sign of fatigue, demonstrating the impact of the ordered dipolar structure on the operational stability of perovskite solar cells.